Rehabilitation of Drug Users in Makassar City - Putri, Safridha Kemala; Salakory, Jacomina Anthonete; Saputra, M. Khalid Fredy; Kristina, Yunita; Ramli, Rachmat; Pannyiwi, Rahmat (International Journal of Health Sciences, 2024)
The spread and abuse of narcotics is a complex problem, which requires comprehensive mitigation efforts involving multidisciplinary, multisectoral cooperation and active community participation carried out continuously, consistently and consistently. Even though in medical science, most classes of narcotics are still useful for treatment, if they are misused or used not according to medical indications or treatment standards, especially if accompanied by illegal distribution, it will have very detrimental consequences for individuals and society at large. The cumulative number of AIDs cases in Indonesia in the second quarter of 2010 was 21,770 cases. The spread of HIV/AIDS among Injection Drug Use/IDUs has reached 8,795 cases. Methadone substitution therapy needs to be carried out with the aim of reducing adverse health, social and economic impacts, reducing the risk of contracting and transmitting HIV to other people, however therapy failure often occurs due to non-compliance or poor adherence. The research is observational with a cross sectional approach. Data were collected using questionnaires through interviews with informants following the therapy program. The results of the study showed good compliance in following therapy. Factors related to compliance in therapy are knowledge, attitudes, motivation, self-efficacy, family role, peer role, and health worker role. Multivariate analysis of multiple Logistic Regression, the most influential factors are motivation and the role of peers.